2012
DOI: 10.1111/j.1467-9930.2011.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Citizenship on the Frontlines: How the Devolution of Canadian Immigration Policy Shapes Service Delivery to Women Fleeing Abuse

Abstract: Always cite the published version, so the author(s) will receive recognition through services that track citation counts, e.g. Scopus. If you need to cite the page number of the TSpace version (original manuscript or accepted manuscript) because you cannot access the published version, then cite the TSpace version in addition to the published version using the permanent URI (handle) found on the record page. This is the author's copy of the pre-press version of this article accepted for publication in Ontario,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
1
39
0
2
Order By: Relevance
“…Scholars have analysed why some cities pass such laws while others develop more expansionist policy (Ramakrishnan and Wong 2010; Chavez and Provine 2009;Hopkins 2010), debated normative questions of whether measures focused on immigrants rightfully lie in federal or subnational policy territory (Spiro 1994;Kobach 2006;Olivas 2007), and studied the roles that non-immigrant actors like police officers, bureaucrats and social service providers play in jurisdictions with politicised legislation (Armenta 2012;Varsanyi et al 2012;Bhuyan 2012;Marrow 2009). Yet the question of how immigrants experience everyday life in restrictive locales remains relatively unexplored.…”
Section: The Intersection Of Legal Restrictions and Assimilationmentioning
confidence: 99%
“…Scholars have analysed why some cities pass such laws while others develop more expansionist policy (Ramakrishnan and Wong 2010; Chavez and Provine 2009;Hopkins 2010), debated normative questions of whether measures focused on immigrants rightfully lie in federal or subnational policy territory (Spiro 1994;Kobach 2006;Olivas 2007), and studied the roles that non-immigrant actors like police officers, bureaucrats and social service providers play in jurisdictions with politicised legislation (Armenta 2012;Varsanyi et al 2012;Bhuyan 2012;Marrow 2009). Yet the question of how immigrants experience everyday life in restrictive locales remains relatively unexplored.…”
Section: The Intersection Of Legal Restrictions and Assimilationmentioning
confidence: 99%
“…). Immigration laws also affect treatment for victims of domestic violence (Bhuyan ; Salcido and Adelman ) and access to government benefits (Yoshikawa and Kalil ; Drachman ). Identity and the mental health of children of immigrants are influenced by immigration laws as well (Delva et al.…”
Section: Conceptual Framework: Immigration Law and The Familymentioning
confidence: 99%
“…For instance, immigration laws affect access to housing, education, employment, and health care (Gonzales 2011;McConnell and Marcelli 2007;Hagan et al 2003). Immigration laws also affect treatment for victims of domestic violence (Bhuyan 2012;Salcido and Adelman 2004) and access to government benefits (Yoshikawa and Kalil 2011;Drachman 1995). Identity and the mental health of children of immigrants are influenced by immigration laws as well (Delva et al 2013;Menjívar and Kanstroom 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that immigrant women in abusive relationships have unequal access to the services provided by the host countries, due to the presence of barriers such as lack of fluency in the host country's language, limited knowledge of available IPV‐related resources and previous experiences of discrimination in their dealings with institutions and professionals . Furthermore, it has been demonstrated that this unequal access to IPV services observed between immigrants and natives interacts with other barriers, such as restricted opportunities to find decent employment or an income which would provide women with financial independence from their partners, length of residence in the host country and legal (or illegal) status …”
Section: Introductionmentioning
confidence: 99%